PERAN KEPALA SEKOLAH PEREMPUAN DALAM MEMIMPIN SATUAN PENDIDIKAN - SUSAN FEBRIANTINA (Jurnal Ilmiah Econosains, 2015)
Abstract School leader is a teacher with added task as the highest leader at school who has to lead his subordinates to the aims of the school. Qualified or unqualified school really depends on school leader, because professional school leader results qualified school and vice versa. There are some qualifications being professional school leader. Principally, school leaders must have a knowledge of and sensitivity for the cross-cultural nature of the community in which they serve and adapt their leadership style accordingly. Recently, the amount of women teachers are higher than men teachers. In fact, the number of woman as school leader is no more than 35% since 2005 till 2010. Many factors influenced this phenomenon, included internal and external factors. Both of the factors correlates each other making an assumption whether woman able and unable being a leader, especially at school. Key words: school leader role, woman school leader.